2016
DOI: 10.1086/684748
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Expressed Genes during Lace Plant Leaf Development

Abstract: Editor: John L. Bowman Premise of research. The lace plant is an excellent and unique model for studying developmentally regulated programmed cell death (PCD) in plants. Perforations form in highly predictable and easily accessible and distinguishable areas in lace plant leaves. However, little is known about the genes involved in regulation of this PCD or leaf development. In this study, for the first time, a general gene expression profile for lace plant leaf development was investigated.Methodology. A cDNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…In spite of the well characterized progression of PCD, little is known about the molecular mechanisms that control lace plant PCD regulation and execution [ 17 , 18 ], in part due to a lack of molecular information for the Aponogetonaceae family. The advancement of comparative RNA sequencing (RNA-Seq) analysis between PCD and NPCD-like cells in other plant models has helped characterize differentially expressed genes (DEGs) that resemble PCD regulators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the well characterized progression of PCD, little is known about the molecular mechanisms that control lace plant PCD regulation and execution [ 17 , 18 ], in part due to a lack of molecular information for the Aponogetonaceae family. The advancement of comparative RNA sequencing (RNA-Seq) analysis between PCD and NPCD-like cells in other plant models has helped characterize differentially expressed genes (DEGs) that resemble PCD regulators.…”
Section: Introductionmentioning
confidence: 99%
“…To date there is only one transcriptome study, Rantong et al (2016) [ 18 ], which investigated lace plant leaf stages using complementary DNA-amplified fragment length polymorphism (cDNA-AFLP). This study identified 79 annotated DEGs which are involved in processes such as photosynthesis, stress responses, pathogen defence, and PCD.…”
Section: Introductionmentioning
confidence: 99%
“…Transcript LesAffx.21605.1.S1_at (FC = −4.03) corresponds to the high mobility group B protein. Differential expression of this HMG type nucleosome/chromatin assembly factor has been associated with plant leaf development (Rantong et al ., 2016) and more recently with thermotolerance in perennial grass (Xu and Huang, 2018). LesAffx.10016.1.A1_at (FC = −2.54) represents a gene of the pseudo response regulator (PRR) family, which are sequentially expressed over the course of the day.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that 40-60 days was the vital phase of fatty acid synthesis and accumulation in castor seeds, displaying various temporal patterns; therefore, those TDFs could be involved in the process of fatty acid synthesis.cDNA-AFLP analysis as a differential display technique could tremendously reduce the number of false positives using restriction enzymes to generate specific tags; thereby, it is a reliable, suitable and economical system to detect differentially expressed transcripts without requiring prior sequence knowledge [8,14]. Rantong et al [19] identified differentially expressed transcripts in lace plant leaf shape during development using cDNA-AFLP, and annotated 79 TDFs related to photosynthesis, biosynthesis pathways, gene regulation and stress responses. Leymarie and Corbineau [20] reported differentially expressed transcripts involved in barley seed germination and dormancy using cDNA-AFLP, and sequenced 25 TDFs.…”
Section: Tdfs Identification and Homology Analysismentioning
confidence: 99%